2002
DOI: 10.1302/0301-620x.84b1.11847
|View full text |Cite
|
Sign up to set email alerts
|

Calcaneal osteotomy and transfer of the tendon of flexor digitorum longus for stage-II dysfunction of tibialis posterior

Abstract: The treatment of acquired flat foot secondary to dysfunction of the posterior tibial tendon (PTT) of stage II, as classified by Johnson and Strom, remains controversial. Joint sparing and soft-tissue reconstructive procedures give good early results, but few studies describe those in the medium-term. We studied prospectively the outcome of surgery in 51 patients with classical stage-II dysfunction of the PTT treated by a medial displacement calcaneal osteotomy and transfer of the tendon of flexor digitorum lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 12 publications
3
57
0
2
Order By: Relevance
“…The AOFAS hindfoot scores improved from 52.2 before surgery to 89 postoperatively, comparable with other series [13] and other alternatives [17,18,25]. Although not validated, our simple patient satisfaction score suggests high patient-rated satisfaction and the longer-term clinical assessment confirmed there was no progression of the deformity.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The AOFAS hindfoot scores improved from 52.2 before surgery to 89 postoperatively, comparable with other series [13] and other alternatives [17,18,25]. Although not validated, our simple patient satisfaction score suggests high patient-rated satisfaction and the longer-term clinical assessment confirmed there was no progression of the deformity.…”
Section: Discussionsupporting
confidence: 77%
“…We have simply mentioned them in the discussion for completeness. However, the AOFAS hindfoot score is validated and the results achieved are comparable with others using the same technique [13] and FDL transfer with os calcis osteotomy [17,18,25] (Table 5). Finally, there were some reservations about the ''extensive'' surgical incisions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…An improvement of the AOFAS hindfoot score from 48 before operation to 84 at follow-up was found in 32 patients treated with medial displacement osteotomy and FDL transfer (Myerson et al 1996). Wacker et al (2002) reported that 43 of 44 patients had excellent or good outcome regarding pain and 36 had good alignment, using the same procedure. Guyton et al (2001) reviewed the results of 26 patients who had undergone this procedure, also for stage 2 (Johnson and Strom 1989) posterior tendon dysfunction, at an average of 32 months and concluded that this procedure provides good medium-term functional and symptomatic results.…”
Section: Discussionmentioning
confidence: 97%
“…Table 1 Ankle-hindfoot scale (100 points total) [6]. Wacker et al [10] präsentierten die Resultate von 51 Patienten, die aufgrund einer Dysfunktion der Sehne des Musculus tibialis posterior, Stadium II, mit einer medialisierenden Kalkaneusosteotomie und einer Verlagerung der Sehne des Musculus flexor digitorum longus behandelt worden waren. 44 Patienten mit einem durchschnittlichen Nachuntersuchungszeitraum von 51 (38-62) Monaten konnten beurteilt werden.…”
Section: Resultsunclassified